BALA’ DALAM TAFSIR ISYARI : STUDI ANALISIS KITAB LATAIF AL-ISYARAT IMAM AL-QUSYAIRI (W. 465 H) - Syamsul Arifin; Ahmad Syukron (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study addresses the common tendency to view balā’ (trial) merely as negative misfortune, whereas the Qur’an and Sufi exegetical traditions often frame trials as instruments for faith formation and spiritual maturity. The research aims to examine the concept of balā’ within Sufi isyārī exegesis by analyzing Imam al-Qushayrī’s (d. 465 H) Laṭā’if al-Isyārāt, focusing on how he interprets Qur’anic passages on trials and what implications follow for religious life. Employing a qualitative library based approach, the primary sources are the Qur’an and Laṭā’if al-Isyārāt, supported by relevant works in Qur’anic exegesis and Sufism; the analysis is conducted through thematic mapping and hermeneutical reading. The findings indicate that al-Qushayrī understands balā’ as a mode of spiritual pedagogy: (1) purification of the self (tazkiyah), (2) advancement through spiritual stations and strengthened servanthood, and (3) unveiling inner meanings that guide the seeker toward ma‘rifah (gnosis). In conclusion, balā’ is not punishment but a means of spiritual transformation fostering patience, contentment, and existential closeness to God.